Antioxidant and Antimicrobial Activities of Codium fragile (Suringar) Hariot (Chlorophyta) Essential Oil and Extracts - Ferda Yilmaz Koz, F.; Ulku Karabay Yavasoglu, N.; Demirel, Zeliha (Asian Journal of Chemistry, 2010)
Macroalgae are rich sources of natural bioactive products. Their secondary metabolites are attracted attends in many fields of life i.e., food, animal feeding, textile, cosmetics, medicine etc. In this study, methanol, dichloromethane and hexane extracts of Codium fragile (Chlorophyta) were tested for antimicrobial and antioxidant activities. Antioxidant effects were evaluated by hydroxyl radical scavenging assay (deoxyribose degradation assay) and b-carotene bleaching assay. The extracts indicated relatively little antioxidant activities, as compared to commercial antioxidants. The composition of the essential oil of C. fragile was also analyzed by GC and GC-MS. Twenty four compounds were identified of C. fragile essential oil and n-tricosane (11.88 %) was determined as major component. Essential oil of C. fragile showed weak antibacterial activity against all gram positive bacteria tested, except methicillin-oxacillin resistant Staphylococcus aureus ATCC 43300. Similarly, all the extracts of C. fragile showed weak antimicrobial activity on tested organisms.